STRATEGI PEMBELAJARAN KITAB SAFINATUNNAJAH DENGAN METODE EKLEKTIK YANG EFEKTIF DINIYAH PONDOK PESANTREN AN-NAJAH - Dwi Muflihah (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
Islamic Boarding School is the oldest educational institution in Indonesia which is synonymous with the study of the Yellow Book. Kyai and ustadz play an important role in organizing learning. This Islamic boarding school uses the Safinatun Najah book study approach to deepen religious knowledge, increase insight and faith. Followed by second grade Santri students and more specifically for the Madrasa final exam in sixth grade. Nowadays, few people are interested in learning the yellow book, because they feel bored and monotonous with the method which only requires listening to the teacher without practicing. This is what makes teachers have to liven up the classroom atmosphere through varied methods. The birth of the eclectic method is the creativity of teachers to make teaching and learning more effective according to the needs of students, make students more active, and create an interactive environment.The focus of the problem in this research is: (1) How is the implementation of learning the book Safinatun Najah through eclectic methods (bandongan, sorogan, memorization and discussion) at Madrasah Diniyah An-Najah Denanyar Jombang (MDAN)?, (2) What are the obstacles and solutions in learning the book Safinatun-Naja through the Eclectic Method at MDAN Denanyar Jombang?This type of research is a case study with a qualitative research approach. The data collection techniques used are observation, interviews and documentation. The data analysis techniques for this research are data reduction, data display (data presentation) and verification (drawing conclusions). The technique for checking the validity of the data is by extending participation, diligent observation, triangulation, and discussion with friends.The results of the research show, (1) Implementation of the learning of the book Safinatun Najah through the eclectic method in stages, namely: the first meeting using the bandongan and sorogan methods, in which the students interpret the material read by the teacher, then they read it again in turns. Next is the memorization and discussion method, students memorize the material they have studied and then hand it over to the teacher, followed by groups to discuss. (2) Existing obstacles are lack of focus, fatigue, and differences in students' abilities. The solutions are: creating comfortable study spaces, ensuring adequate sleep, giving assignments according to ability, and dividing students into groups based on ability. This research is expected to make a positive contribution, especially to MDAN Denanyar Jombang.